2015
DOI: 10.3389/fmolb.2015.00009
|View full text |Cite
|
Sign up to set email alerts
|

Using docking and alchemical free energy approach to determine the binding mechanism of eEF2K inhibitors and prioritizing the compound synthesis

Abstract: A-484954 is a known eEF2K inhibitor with submicromolar IC50 potency. However, the binding mechanism and the crystal structure of the kinase remains unknown. Here, we employ a homology eEF2K model, docking and alchemical free energy simulations to probe the binding mechanism of eEF2K, and in turn, guide the optimization of potential lead compounds. The inhibitor was docked into the ATP-binding site of a homology model first. Three different binding poses, hypothesis 1, 2, and 3, were obtained and subsequently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
(75 reference statements)
2
6
0
Order By: Relevance
“…Even in the two cases where these values differ by over 1.0 kcal/mol, it is worth noting the correct prediction on the qualitative impact of the modifications (i.e., whether they would improve or reduce potency). Therefore, the TI outcomes for cruzain agreed with other retrospective studies in which the error of the calculated free energy of binding was around 1–2 kcal/mol relative to the experimental data. These results are especially encouraging when we consider that the determination of ligand protonation state was not trivial and most ligands contained halogen atoms for which the interactions are still challenging for force fields …”
Section: Discussionsupporting
confidence: 80%
“…Even in the two cases where these values differ by over 1.0 kcal/mol, it is worth noting the correct prediction on the qualitative impact of the modifications (i.e., whether they would improve or reduce potency). Therefore, the TI outcomes for cruzain agreed with other retrospective studies in which the error of the calculated free energy of binding was around 1–2 kcal/mol relative to the experimental data. These results are especially encouraging when we consider that the determination of ligand protonation state was not trivial and most ligands contained halogen atoms for which the interactions are still challenging for force fields …”
Section: Discussionsupporting
confidence: 80%
“…According to the specific interaction pattern of mitoxantrone and eEF-2K, we found that there are five hydrogen-bond interactions (Arg140, Lys170, Ile232, Glu 233, and Gly 234) between them (Fig. 6C ), and four residues have been reported in the literatures 26 29 , which further demonstrated that mitoxantrone is likely to be a potent inhibitor of eEF-2K.
Fig.
…”
Section: Resultssupporting
confidence: 59%
“…There is clearly an acute need to identify better eEF2K inhibitors as tool compounds to explore the roles of eEF2K in normal cell physiology and in disease. Such efforts have been hindered by the lack of a 3-dimensional structure for eEF2K but will be aided by the development of a homology model of eEF2K based on the known structures of two other members of the α-kinase family [39] .…”
Section: Wwwchinapharcom Liu R Et Almentioning
confidence: 99%